Metonymy in the gastronomic configuration of Quechua of Aurahuá- Chupamarca: a cognitive study - Gálvez Astorayme, Isabel (2020)
This article addresses the semantic aspects involved in the configuration of the gastronomy of Aurahuá-Chupamarca (districts of the province of Castrovirreyna, region of Huancavelica). The semantic-cultural motivations underlying the linguistic expressions referred to gastronomic entities are identified, which correspond notoriously with metonymic mechanisms. The study is based on the theoretical And methodological principles of cognitive linguistics (Lakoff and Johnson, 1980; Lakoff, 1987; Langacker, 1987; Ibarretxe-Antuñano and Valenzuela, 2012; Evans and Green, 2006, among others). The metonymies show how Quechua speakers categorize the indicated gastronomic entities. The way in which linguistic forms are associated with Quechua cuisine is described and explained.